Regulatory reform: Economic analysis and British experience - Armstrong, M; Cowan, S; Vickers, J (MIT Press, 1994)
Considers the main issues in regulatory reform and assesses regulatory reform in Great Britain. Addresses the basic static issues in monopoly regulation; multiproduct and dynamic issues in the regulation of monopoly, including the implications of relaxing the assumptions that the regulator is benevolent and able to commit to future regulatory policy; the efficiency and effectiveness of competition relative to regulation; interactions between competition and regulation, including franchising, the regulation of a dominate firm that faces a relatively small amount of competition, and cross-market links that arise when a multiproduct firm operates in both monopolistic and competitive markets; and issues of competition and regulation policy in vertically related industries. Describes and assesses the British use of price cap regulation RPI - X. Presents case studies of regulatory reform in the U.K. telecommunications, gas, electricity, and water industries, covering the economic characteristics of the industries, the broad policy options, the choices between those options made in Britain, and lessons from the resulting experience. Armstrong is at the University of Southampton. Cowan is at Worchester College, Oxford. Vickers is at All Souls College, Oxford. Name and subject indexes.